2011
DOI: 10.1519/jsc.0b013e3182281939
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and Lateral Forces Applied to the Bar during the Bench Press in Novice Lifters

Abstract: The purpose of this study was to determine the vertical and lateral forces applied to the bar during a maximal and a submaximal effort bench press lifts. For this study, 10 male and 8 female recreational lifters were recruited (mean height: 1.71 ± 0.08 m; mass: 73.7 ± 13.6 kg) and were asked to perform a maximal and submaximal (80% of maximal lift) bench press. These lifts were performed with a bar instrumented to record forces applied to it, via the hands, in the vertical direction and along the long axis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 6 publications
2
15
1
Order By: Relevance
“…For the DBP, the lower 10RM load might be associated to the greater stability requirements that decreases the net torque and the ability to lift the weight. 6 In the current study, there were no significant differences in the repetitions per set, training volume and total work, between bench press modes. Our results were in contrast with the Augustsson et al 17 who observed a decrease in muscle electrical activity and a decrease in repetition performance when a multijoint exercise (leg press) was preceded by a single-joint exercise (leg extension).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…For the DBP, the lower 10RM load might be associated to the greater stability requirements that decreases the net torque and the ability to lift the weight. 6 In the current study, there were no significant differences in the repetitions per set, training volume and total work, between bench press modes. Our results were in contrast with the Augustsson et al 17 who observed a decrease in muscle electrical activity and a decrease in repetition performance when a multijoint exercise (leg press) was preceded by a single-joint exercise (leg extension).…”
Section: Discussioncontrasting
confidence: 50%
“…Despite similar kinematics, each bench press modality may promote distinct myoelectric responses. 3 Bench press using barbell promotes lateral forces directed toward the ends of the barbell that equals approximately 25% of the vertical force, independent of the load intensity 6 . Lateral forces on the barbell promote activity in the triceps brachii.…”
Section: Introductionmentioning
confidence: 99%
“…The greater moment arm on the elbow will logically create a higher degree of lateral forces and a lesser amount of the total forces produced put vertically on the barbell. Duffey and Challis (2011) found in novice lifters that the lateral force production in a bench press was between 22% and 29% of the vertical force produced. When relating this to the present study, we see that if the total force production is the same in all three grip widths throughout the lift, the differences in moment arms will cause the vertical forces to be different because of a greater lateral force.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, by including the lateral forces as measured in the study of Duffey and Challis (2011), the direction of the total force production can be measured, which can show during the lift if this total force direction goes laterally, medially or directly through the elbow joint ( Figure 6). These differences in direction of total Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Using asymmetric loads, lateral forces had to be generated to compensate for the disruptive momentum caused by the de-loaded side. Triceps brachii can generate lateral forces with the bench press (Duffey and Challis 2011 ). The lower triceps brachii activation on the loaded side, contrasting with the similar activation across the conditions on the de-loaded side, was most likely an attempt to maintain a centered barbell.…”
Section: Discussionmentioning
confidence: 99%